PENDAMPINGAN PUBLIKASI ILMIAH BAGI MAHASISWA MAGISTER TEKNIK ELEKTRO, JAKARTA GLOBAL UNIVERSITY - Agung, Pangestu; Ahda Sabila, Yusuf; Rizky Farmasita, Budiastuti; Yanuar Zulardiansyah, Arief; Rosyid Ridlo, Al Hakim (STKIP PGRI SITUBONDO, 2023)
Scientific publications are one of the outputs in organizing academic activities, especially in the master's program organized by Jakarta Global University (JGU). Scientific publications are intended for students who want to complete their thesis, so it is necessary to hold scientific publication assistance activities for JGU electrical engineering master's students. The stages passed include activity planning, implementation, and evaluation of activities. Indicators of achievement from this mentoring activity include students being able to gradually carry out the manuscript submission process through the open journal system (OJS), following a series of peer reviews from peer review partners to improve their manuscripts, and students have understood the scientific publication process so that they can be published online at OJS.